Association between Serum Alp Levels and Pre- Operative LDH towards Clinical Prognosis of Osteosarcoma Patients in H. Adam Malik Hospital, Medan - Gerhard Christoffel Tampubolon; Otman Siregar; Andriandi (Talenta Publisher, 2023)
Background: Osteosarcoma remains a challenging disease, especially for young patients, due to its tendency to spread to the lungs and resist treatment. Identifying reliable markers at diagnosis could help doctors start more effective treatment earlier and improve patient outcomes. Two blood markers, ALP and LDH, may offer insight into a patient’s prognosis. Objective: This study explored whether pre-surgery levels of ALP and LDH could predict survival in osteosarcoma patients. Methods: Researchers reviewed medical records of patients diagnosed with osteosarcoma at RSUP Haji Adam Malik Medan from 2015 to 2017. This retrospective study included those who met the necessary criteria and had complete data. Results: The study found no strong evidence linking ALP or LDH levels to five-year survival. ALP had a very weak negative correlation with survival (r = -0.019), while LDH showed a weak positive correlation (r = 0.093). Median ALP was 212 U/L; LDH was 489 U/L. Sensitivity and specificity were moderate for both markers. Conclusion: There is no significant relationship between ALP and LDH with five-year survival.